Paper-based integrated evaporation device for efficient solar steam generation through localized heating. (August 2019) - Guo, Cheng-Long; Miao, En-Dong; Zhao, Jia-Xu; Liang, Lin; Liu, Qi
Graphical abstract: Highlights: Paper-based integrated evaporation device (IED) was designed. Self-hardening polyurethane foam was used for thermal insulation. The IED exhibited thermal conversion efficiency of 88.1% at 1 sun. Excellent reusability was demonstrated by a 10-cycle experiment. Abstract: The all-in-one solar steam generation device renders a feasible technical support for freshwater supply in arid areas, where traditional large-scale desalination cannot be applied. In this work, we designed and assembled a paper-based integrated evaporation device (IED) for efficient solar steam generation, in which the self-hardening polyurethane foam was ingeniously fixed on the carbon nanotube (CNT) loaded filter paper connecting with four paper belts to perfectly integrate light absorption, water supply and thermal insulation into one device. Moreover, the effects of CNT concentration and illumination intensity on evaporation performance were experimentally investigated. The results showed that the maximum thermal conversion efficiency of the IED was as high as 88.1% at 1 kW m −2 . Our research indicated that the IED as an easily-enlarged and all-in-one evaporation device was one of the ideal choices for applications in solar steam generation and provided a new resource for seawater desalination.